Dynamic micro-organization of P2X7 receptors revealed by PALM based single particle tracking - Shrivastava, Amulya N.; Rodriguez, Pamela C.; Triller, Antoine; Renner, Marianne (Frontiers in Cellular Neuroscience, 2013)
Adenosine triphosphate (ATP)-gated P2X7 receptors (P2X7Rs) are members of the purinergic receptor family that are expressed in several cell types including neurons. A high concentration of ATP is required for the channel opening of P2X7Rs compared to other members of this receptor family. Recent work suggests that ATP binding to members of the P2X receptor family determines the diffusion and localization of these receptors on the plasma membrane of neurons. Here, we employed single particle tracking photoactivated localization microscopy (sptPALM) to study the diffusion and ATP-dependence of rat P2X7Rs. Dendra2-tagged P2X7Rs were transfected in hippocampal neurons and imaged on proximal dendrites. Our results suggest the presence of two populations of P2X7Rs within the extra-synaptic membrane: a population composed of rapidly diffusing receptors and one stabilized within nanoclusters (~100 nm diameter). P2X7R trajectories were rarely observed at synaptic sites. P2X7R mutations in the ATP-binding site (K64A) or the conserved phosphorylation site (K17A) resulted in faster- and slower-diffusing receptors, respectively. Furthermore, ATP differentially accelerated wild type and K17A-mutant receptors but not K64A-mutant receptors. Our results indicate that receptor conformation plays a critical role in regulating ATP-mediated changes in P2X7R diffusion and micro-organization.